MRI observations at return to play of clinically recovered hamstring injuries - Reurink, G.; Goudswaard, G. J.; Tol, J. L.; Almusa, E.; Moen, M. H.; Weir, A.; Verhaar, J. A. N.; Hamilton, B.; Maas, M. (British Journal of Sports Medicine, 2014)
Background: Previous studies have shown that MRI of fresh hamstring injuries have diagnostic and prognostic value. The clinical relevance of MRI at return to play (RTP) has not been clarified yet.